Knowledge and Attitudes of Female Students at Stikes Sehat Medan on Human Papillomavirus Infection and Vaccination - Putra, Adistyra Arya; Pane, Abdul Harris; Anggreni, Siska; Anshari, Zaim (International Journal of Public Health Excellence (IJPHE), 2024)
Cervical cancer is a malignancy that can occur in a woman's cervix and has a fairly high mortality rate. The virus that causes cervical cancer is Human Papillomavirus (HPV). One way to prevent HPV infection is to get the HPV vaccination. The purpose of this research is to analyze the relationship between knowledge and attitudes of STIKes Sehat Medan students regarding Human Papillomavirus infection and vaccination. The method used is descriptive analytical research with a cross-sectional approach, sampling using a total sampling method of 124 STIKes Sehat Medan students in 2024. Data analysis used the Spearman correlation test. The results of this study showed that of the 124 respondents, 95 students (76.6%) of STIKes Sehat Medan students had good knowledge about HPV infection and 102 people (82.3%) had a good attitude about HPV infection. Furthermore, as many as 118 people (95.2%) of STIKes Sehat Medan students had good knowledge about HPV vaccination and as many as 102 people (82.3%) had a good attitude about HPV vaccination. Based on the results of the Spearman correlation test, the relationship between knowledge and attitudes of STIKes Sehat Medan students regarding HPV infection in 2024, the value of p=0.010 was obtained, which means that there is a significant relationship between the knowledge and attitudes of STIKes Sehat Medan students regarding HPV infection and the value of p=0.015 was obtained, which is This means that there is a significant relationship between the knowledge and attitudes of STIKes Sehat Medan students regarding HPV vaccination.